resolva o sistema: a+b=-15
3a=-45+5b, pelo metodo de substituição.
Soluções para a tarefa
Respondido por
0
a+b=-15
3a=-45+5b
a+b=-15
ou
a=-15-b
3*(-15-b)=-45+5b
-45-3b=-45+5b
2b=0
b=0
a+b=-15
a=-15+0
a=-15
(-15, 0 )
3a=-45+5b
a+b=-15
ou
a=-15-b
3*(-15-b)=-45+5b
-45-3b=-45+5b
2b=0
b=0
a+b=-15
a=-15+0
a=-15
(-15, 0 )
Respondido por
0
substituição
![\left \{ {{a+b=-15} \atop {3a=-45+5b}} \right. \left \{ {{a+b=-15} \atop {3a=-45+5b}} \right.](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Ba%2Bb%3D-15%7D+%5Catop+%7B3a%3D-45%2B5b%7D%7D+%5Cright.+)
isolar
a=-15-b
subst/ em
![3a=-45+5b
3a=-45+5b](https://tex.z-dn.net/?f=3a%3D-45%2B5b%0A+)
![3(-15-b)=-45+5b \\ -45-3b=-45+5b \\ -3b-5b=-45+45 \\ -8b=0 \\ b=0 3(-15-b)=-45+5b \\ -45-3b=-45+5b \\ -3b-5b=-45+45 \\ -8b=0 \\ b=0](https://tex.z-dn.net/?f=3%28-15-b%29%3D-45%2B5b+%5C%5C+-45-3b%3D-45%2B5b+%5C%5C+-3b-5b%3D-45%2B45+%5C%5C+-8b%3D0+%5C%5C+b%3D0)
como
![a=-15-b \\ a=-15-0 \\ a=-15 a=-15-b \\ a=-15-0 \\ a=-15](https://tex.z-dn.net/?f=a%3D-15-b+%5C%5C+a%3D-15-0+%5C%5C+a%3D-15)
S={(-15,0)}
isolar
a=-15-b
subst/ em
como
S={(-15,0)}
Perguntas interessantes